DINAMIKA BENTUKAN LAHAN FLUVIAL AKIBAT SEDIMENTASI DI SUNGAI GRINDULU, SEGMEN ARJOSARI-PACITAN (Fluvial landform dynamics caused by sedimentation of Grindulu River, Arjosari-Pacitan Segment) - Arina Miardini (Center for Implementation of Standards for Environmental and Forestry Instruments Solo, 2019)
ABSTRACTLandforms experience dynamics during the geomorphological process. The fluvial process occurs due to the flow of water from erosion, erosion transportation, and sedimentation activities. Sedimentation material is resulted from erosion transported through the river. Later the deposited erosion will produce landform variations. Therefore, information of landform dynamic is important in controlling runoff and floods. The purpose of this study was to identify and determine the dynamics of the fluvial landform in Grindulu River, Arjosari-Pacitan Segment. The method used is combination of desk analysis and field surveys. The desk analysis is conducted to identify the types of landforms through visual interpretation of SPOT-7 Imagery, while field surveys are to determine sample units using purposive sampling. Based on landform analysis in the Arjosari-Pacitan Segment, there were five fluvial landforms processes due to sedimentation namely point bar, channel bar, flood plain, meandering, and natural levee. The dynamics that occur are dominated by the aggradation process, namely the addition of flood plain landform area of 0.872 ha (0.216%), channel bar of 0.091 ha (0.019%), and natural levee of 0.014 ha (0.002%). The identification of landforms can be used as a basis in spatial planning to optimize water system in watershed.Keywords: landform; fluvial; sedimentation; Grindulu Watershed ABSTRAKBentuklahan mengalami dinamika selama terjadinya proses geomorfologi. Proses fluvial terjadi akibat aliran air dari aktivitas erosi, transportasi, dan sedimentasi. Material sedimentasi berasal dari hasil erosi yang terangkut melalui sungai yang kemudian diendapkan yang nantinya akan menghasilkan variasi bentuklahan. Dengan demikian informasi mengenai dinamika bentuklahan sangat penting untuk mengendalikan aliran permukaan dan banjir. Tujuan penelitian ini adalah untuk mengidentifikasi dan mengetahui dinamika bentuklahan hasil proses fluvial di Sungai Grindulu, Segmen Arjosari-Pacitan. Metode yang digunakan yaitu kombinasi antara desk analysis (dilakukan untuk mengidentifikasi jenis-jenis bentuklahan melalui interpretasi citra SPOT-7) dan survey lapangan (menentukan unit sampel secara purposive sampling). Hasil analisis bentuk lahan pada Segmen Arjosari-Pacitan diperoleh lima bentuklahan proses fluvial akibat sedimentasi yaitu point bar, channel bar, flood plain, meandering, dan natural levee. Dinamika yang terjadi didominasi oleh proses agradasi yaitu penambahan luasan bentuklahan flood plain sebesar 0,872 ha (0,216%), channel bar sebesar 0,091 ha (0,019%), dan natural levee sebesar 0,014 ha (0,002%). Identifikasi bentuklahan ini dapat dijadikan dasar dalam perencanaan tata ruang untuk mengoptimalkan tata air dalam DAS.Kata kunci: bentuklahan; fluvial; sedimentasi; DAS Grindulu